How Does Group-Decision Making Affect Subsequent Individual Behavior? - Philipp Dörrenberg; Christoph Feldhaus (Center for Economic Studies and ifo Institute (CESifo), 2022)
Do groups and individuals behave differently in dictator games with varying deservingness of the recipient? Does the involvement in group-decision making affect the decisions of group members in subsequent individual decisions? We address these questions using a controlled dictator-game experiment and find the following main results. First, groups and individuals are not different w.r.t. their dictator-game decisions and recipient deservingness does not have a different effect on groups than on individuals. Second, participants who were previously part of a group decision process are more generous in a subsequent individual-level decision than participants who previously made individual decisions. We exploit the chat protocols of group discussions to shed light on the mechanism behind this result. Consistent with moral balancing, we show that the effect of group-decision making on subsequent individual decisions is driven by subjects who intent to make good for the initial group decision.
Keywords: C91; C92; D91; 330; group-decision making; dictator game; recipient deservingness; moral balancing